2007
DOI: 10.1590/s0034-72992007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações vestibulococleares em pacientes com diabetes melito tipo I

Abstract: Gl ucose metabolism has a significant impact on inner ear physiology, and small changes may result in hearing and balance disorders. Aim: To investigate vestibulocochlear symptoms in patients with type I diabetes mellitus. Study design: a cross-sectional study of a contemporary group. Material and Method: 30 patients referred from Clinical Hospital-UFPR to the Laboratory of Otoneurology-UTP between Mar/2004 to Feb/2005 were evaluated. The following procedures were carried out: a medical history, otological ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
1
1
4
Order By: Relevance
“…Similarly, no significant results were found regarding associations between vertigo and caffeine abuse, alcohol consumption alcoholism and smoking, different from what is found in the literature (Klagenberg, et al, 2007;Wada, et al, 2017).…”
Section: Causes Of Dizzinesscontrasting
confidence: 99%
“…Similarly, no significant results were found regarding associations between vertigo and caffeine abuse, alcohol consumption alcoholism and smoking, different from what is found in the literature (Klagenberg, et al, 2007;Wada, et al, 2017).…”
Section: Causes Of Dizzinesscontrasting
confidence: 99%
“…Discretas variações na concentração da glicose podem produzir alterações no equilíbrio eletrolítico causando sintomas vestibulares, auditivos ou ambos. 5,7 Fonseca e Davidsohn 5 , ao compararem grupos de indivíduos com tontura e assintomáticos, constataram que o grupo com queixa espontânea ou questionada de tontura apresentava alterações no metabolismo da glicose em 65% dos casos. Já entre os pacientes do grupo sem queixa de tontura, 30% apresentavam alterações do metabolismo da glicose, sugerindo que a tontura é um bom indicador de alteração do metabolismo da glicose e a alteração do metabolismo da glicose é um bom indicador de alteração do exame vestibular.…”
Section: Discussionunclassified
“…Klagenberg et al observed the prevalence of changes in the peripheral vestibular system and the peripheral vestibular deficit syndrome 35 . This result is consistent with other studies that also found changes in the vestibular exam 36,37 .…”
mentioning
confidence: 99%